KNOWLEDGE AND PRACTICE OF NURSES REGARDING TRACHEOSTOMY CARE - AMIR, S; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Tracheostomy is a common procedure in critical care settings for patients requiring prolonged ventilation or airway management. Nurses play a crucial role in tracheostomy care, which demands comprehensive knowledge and adherence to evidence-based practices to prevent complications. Objective: This study aimed to assess the knowledge and practices of nurses regarding tracheostomy care at Jinnah Hospital Lahore. Methods: A descriptive cross-sectional study was conducted from January 2024 to July 2024 at Jinnah Hospital Lahore. A total of [specify sample size, e.g., 150] registered nurses working in different wards and intensive care units (ICUs) were selected through simple random sampling. Data were collected using a structured questionnaire, which included sections on demographic information, knowledge, and practices. Knowledge and practice scores were categorized as good, moderate, or poor. Data analysis was performed using SPSS version 25.0, employing descriptive statistics and chi-square tests to identify associations between variables. Results: The study revealed that 60% of the nurses had moderate knowledge regarding tracheostomy care, while 25% demonstrated good knowledge, and 15% had poor knowledge. In terms of practice, 54.7% of nurses reported moderate adherence to tracheostomy care protocols, 30% had good practices, and 15.3% demonstrated poor practices. A significant association was found between formal training in tracheostomy care and higher knowledge and practice scores (p < 0.05). Conclusion: The findings indicate that most nurses possess moderate knowledge and practices concerning tracheostomy care, with notable gaps in training and adherence to standardized protocols. The study highlights the need for structured training programs and continuous professional development to enhance nurses' competency in tracheostomy care and improve patient outcomes.